Marked Independent Relationship between Circulating Interleukin-6 Concentrations and Endothelial Activation in Rheumatoid Arthritis - Patrick H. Dessein; Ahmed Solomon; Angela J. Woodiwiss; Gavin R. Norton; Linda Tsang; Miguel A. Gonzalez-Gay (Mediators of Inflammation)
We examined the potential impact of conventional compared with nonconventional cardiovascular risk factors including interleukin-6 levels on endothelial activation in RA. Circulating soluble E-selectin, vascular cell adhesion molecule-1, intercellular adhesion molecule-1, and monocyte chemoattractant protein-1 concentrations were measured in 217 African patients (112 black and 105 white) with RA. In comprehensive confounder adjusted mixed regression models, 5 conventional and 4 nonconventional cardiovascular risk factors were associated (P=0.05 to <0.0001) with endothelial activation. Interleukin-6 was the only risk factor related to each endothelial activation molecule and independently contributed by 18% and significantly more than other risk factors to the variation in overall endothelial activation as estimated by an SD (z) score of endothelial activation molecule concentrations. The independent interleukin-6-overall endothelial activation relationships were reproduced in various subgroups. Interleukin-6 concentrations relate consistently, markedly, and to a larger extent than other cardiovascular risk factors to endothelial activation in RA. Assessment of interleukin-6 concentrations may enhance cardiovascular risk stratification in RA.